Radio spots with agroclimatic information from the Local Technical Agroclimatic Committees (LTAC) for the ASO 2022 climate forecast in Eastern Guatemala (Spanish) - Hernández Quevedo, Mónica; Navarro Racines, Carlos Eduardo (2022)
Climate information produced and disseminated through the Local Technical Agroclimatic Committees (MTAs) is shared via radio in eastern departments of Guatemala for the forecast ASO 2022.